ナンキョク ヒガシ オングル トウ コケ グンラク ノ カコ 17 ネンカン ノ イチジ セイサンリョウ ノ スイテイ - 伊野, 良夫; イノ, ヨシオ; Ino, Yoshio (1983)
P(論文) 南極生態系の機構解明のため, コケ群落の一次生産量の推定を試みた。1982年1月に昭和基地で東オングル島産のコケ群落の光合成, 呼吸速度を赤外線ガス分析計を使って同化箱法で測定した。ヤノウエノアカゴケ(Ceratodon purpureus), キョクチセンボンゴケ(Pottia heimii), オオハリガネゴケ(Bryum pseudotriquetrum)の混生群落で, それらの表面はらん藻と地衣におおわれていた。総光合成速度と呼吸速度は, それぞれ日射量と気温との積(R-T index)に二次式で近似できた。1959年11月から1981年1月まで, 基地閉鎖期間を除く17回の夏(11月から3月)の昭和基地の気象資料を用いて, コケ群落の総生産量と呼吸消費量を計算した。両者の差を純生産量とすると, 平均純生産量は3.7g dw/m^2・yr, 最大値, 最小値は12.8,-16.2g dw/m^2・yrであった。 This investigation is a part of the works to make clear the function of an Antarctic ecosystem. The photosynthetic activity and the respiration of moss community sampled on East Ongul Island, East Antarctica, were measured in January 1982 at Syowa Station with an infrared gas analyzer. Three species of mosses, Ceratodon purpureus, Pottia heimii and Bryum pseudotriquetrum were included in the community. The surface of all moss communities was covered with blue-green algae and lichens, and the growth condition of moss communities looked very poor. Positive correlations were observed between the gross photosynthetic rate or respiration rate and the R-T index, which is the product of daily radiation amount and daily mean air temperature. The net production rates in summer, from November to March, were estimated by the use of meteorological data for 17 years. Mean net production rate of moss community was 3.7g dw/m^2・yr, and the maximum and the minimum rates were 12.8 and -16.2g dw/m^2・yr, respectively. departmental bulletin paper